Opinion Shopping Sebagai Pemoderasi Pengaruh Financial Distress Pada Opini Audit Going Concern - Yanti, Ni Putu Purnami Eka; Dwirandra, A. A. N. B. (E-Jurnal Akuntansi; Vol 26 No 1 (2019)DO - 10.24843/EJA.2019.v26.i01.p05, 2019)
The acceptance of a going concern audit opinion is important to study because when economic conditions fluctuate, investors expect the auditor to provide an early warning of the company's financial failure. The purpose of this study was to determine the ability of opinion shopping to moderate the influence of financial distress on going-concern audit opinion. The study was conducted at manufacturing companies listed on the Indonesia Stock Exchange in 2013-2017. The number of samples in this study were 110 companies. The data collection method used is a non probability sampling method with a purposive sampling technique. The data analysis technique used is logistic regression analysis and MRA. The results of the analysis found that financial distress had no effect on the going-concern audit opinion. Companies that experience financial difficulties do not necessarily accept the going concern audit opinion because companies can conduct strategic actions by managing assets efficiently. Opinion Shopping is not able to moderate financial distress in going-concern audit opinion. The opinion shopping practice did not affect the acceptance of non going concern audit opinion. Keywords:  financial distress, opinion shopping, going concern audit opinion.